Spatial variations in in-migration and out-migration patterns in Bihar, India - Suman Lata; Ayesha Jamal (National Geographical Journal of India, 2025)
The present study aims to analyze the spatial patterns of in-migration and out-migration in Bihar between 2001 and 2011, using place-of-birth data from the Census of India. To explore district-level in-migration dynamics, the five leading origin states for each district were identified and ranked based on their share of the total in-migrant population in 2011. The findings indicate that, in 2011, intra-district migration constituted the largest share of total migration in Bihar, accounting for nearly 68 percent, followed by inter-district migration at approximately 27 percent. Notably, interstate migration declined from 7.9 percent in 2001 to just 4 percent in 2011. Whereas the number of total out-migrants of Bihar observed an increase from 5.5 million in 2001 to 7.9 million in 2011 with a positive growth ( 44 percent). The primary destination states for these migrants were Jharkhand, West Bengal, Uttar Pradesh, Maharashtra, and the National Capital Territory (NCT) of Delhi, which together absorbed around 69 percent of Bihar’s total out-migrants. The primary destination states for these migrants were Jharkhand, West Bengal, Uttar Pradesh, Maharashtra, and the National Capital Territory (NCT) of Delhi, which together absorbed around 69 percent of Bihar’s total out-migrants. Conversely, in-migration to Bihar declined over the decade, with the total number of immigrants falling from 1.5 million in 2001 to 1.0 million in 2011, representing a negative growth of 23.5 percent. The states like Jharkhand, Uttar Pradesh, West Bengal, Assam, and NCT of Delhi were major origin states sending migrants to Bihar comprising about 95 percent share in total in-migrants. The study revealed that in terms of ranking, the highest in-migration in Bihar occurred from three neighbouring states namely, Jharkhand, West Bengal, and Uttar Pradesh.